Effects of social media use on employment anxiety among Chinese youth: the roles of upward social comparison, online social support and self-esteem - Jin, Ting; Chen, Yanshan; Zhang, Ke (Frontiers in Psychology, 2024)
Based on the continuous development of new media and mobile communication technologies, social media has significantly influenced people’s daily thoughts and behaviors. For young people, social media is a platform for social interaction, and studies have found that social media helps Chinese graduates find employment. This study examined how social media use and its related factors affect employment anxiety. The data was collected from 1,204 Chinese youth through an online survey. The results showed that: (1) the intensity of social media use had a positive predictive effect on employment anxiety; (2) upward social comparison and online social support individually separately mediate the positive relationship between the intensity of social media use and employment anxiety; and (3) self-esteem negatively moderates the effect of upward social comparison and effect of online social support on employment anxiety. The study underscores the importance of reasonable social media usage strategies, positive social perception, and healthy self-perception for fostering a positive employment mindset among youth.